MOISTURE ADSORPTION AND EFFECT OF ADSORBED WATER ON THE POWDER AND COMPACTION PROPERTIES OF RANITIDINE HYDROCHLORIDE - (:unkn) unknown (GOVI-VERLAG GMBH, 1991)
Moisture adsorption properties of ranitidine hydrochloride were investigated. The amount of water adsorbed was very small up to 75% relative humidity (RH), however, after this value (critical RH), an abrupt increase was observed in the moisture adsorption. Addition of excipients changed the water uptake levels of drug. Furthermore moisture adsorption proportionally increased with the amount of Avicel(R) and corn starch. In the second part of this study the effect of adsorbed water on powder and compaction properties of ranitidine hydrochloride was studied. The powder and compaction properties of the drug were changed by water adsorption.
Keywords: STABILITY; STRENGTH; TABLETS